2022
DOI: 10.1108/jepp-01-2022-0010
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and competition: does internationalisation provide advantages for the family firms in a transition economy?

Abstract: PurposeKosovo has experienced a radical shift from a centrally planned economy to a market economy and built institutions from scratch. During the institutional building process, due to inconsistencies in institutional reforms, firms faced several challenges in competing in the domestic market and engaging in exporting activities. The purpose of the study is threefold. First, to examine how institutional settings influence family firms’ success; second, how and which types of strategic behaviours family firms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…Regarding entrepreneurship, institutional environments in developing economies (e.g., Turkey) are considered more favorable institutional contexts (Guerrero et al 2021 ) compared to those in transition economies (e.g., Kosovo). Countries characterized by the latter are represented by a low-income institutional context unfavorable to entrepreneurship, derived from the uncertainty of policies and other institutional settings (Kryeziu and Coşkun 2018 ; Coşkun et al 2022 ; Kryeziu et al 2022 ; Patel and Wolfe 2022 ). On the other hand, the developing and transition economies–the context of this study–are characterized by uncertainties present in a weak institutional environment.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding entrepreneurship, institutional environments in developing economies (e.g., Turkey) are considered more favorable institutional contexts (Guerrero et al 2021 ) compared to those in transition economies (e.g., Kosovo). Countries characterized by the latter are represented by a low-income institutional context unfavorable to entrepreneurship, derived from the uncertainty of policies and other institutional settings (Kryeziu and Coşkun 2018 ; Coşkun et al 2022 ; Kryeziu et al 2022 ; Patel and Wolfe 2022 ). On the other hand, the developing and transition economies–the context of this study–are characterized by uncertainties present in a weak institutional environment.…”
Section: Methodsmentioning
confidence: 99%
“…A large group of external factors is associated with local or foreign market and/or industry conditions (Cieślik and Kaciak, 2011; Cunningham et al , 2012). Regarding local conditions, authors have found that smallness of the home market can push firms abroad (Coşkun et al , 2022; Nowiński and Rialp, 2013). Moreover, decreased local demand (Durand and Lautier, 2013) or local consumers’ low interest for the firm’s products or services (Mihailova et al , 2020) can motivate them to seek for more promising foreign markets (Stoian et al , 2016).…”
Section: External Factors Internal Motivators and Actions Affecting C...mentioning
confidence: 99%
“…From foreign market and/or industry conditions, studies have mentioned favourable economic policies like trade liberalization (Békés and Muraközy, 2012), financial incentives and a favourable investment climate (Gorynia et al , 2015). Foreign customers’ willingness to pay (Nowiński and Rialp, 2013) or buy more (Ciszewska-Mlinaric et al , 2016; Elo, 2016), and, thus, the potential to earn higher profits (Coşkun et al , 2022; Ďaďo et al , 2015; Fonfara et al , 2021; Vissak and Zhang, 2016) can also motivate firms to enter foreign markets. In addition, geographical proximity (Ciszewska-Mlinaric et al , 2016), availability of low-cost resources (Gorynia et al , 2015) and lack of language barriers (Panibratov and Latukha, 2014) can affect location choice.…”
Section: External Factors Internal Motivators and Actions Affecting C...mentioning
confidence: 99%
See 1 more Smart Citation
“…The sample of this study consists of exporting Small and Medium Enterprises firms that operate in a transition economy, Kosovo. However, the number of firms engaged in exporting activities in the case of Kosovo is low (Kryeziu et al, 2022;Cos ¸kun et al, 2022). This is due to the structural reforms and the challenges that firms from Kosovo face (Kryeziu and Cos ¸kun, 2018) and factors at the firm level (Krasniqi and Mustafa, 2016).…”
Section: Data Collection and Samplementioning
confidence: 99%